Absolute poverty measurement with minimum food needs: A new inverse method for advanced economies - Bálint Menyhért (European Commission, 2022)
This paper explores the feasibility of calculating absolute poverty lines on the basis of minimum food expenditures in developed countries. It makes three important contributions. First, it demonstrates that standard statistical methods used in the developing world deliver either inadequate poverty estimates in rich countries characterised by a relatively low food expenditure share. Second, it proposes a new simulation-based method that focuses on the non-food Engel curve and uses available food reference budgets not as inputs but as targeted reference points for the calculations. Finally, an empirical application of the new method using household budget survey data from Italy shows that resulting poverty estimates are in line with the official figures of the Italian Statistical Office in terms of both the poverty rate and the poverty profiles. The proposed method is therefore well suited to produce robust and consistent absolute poverty measures in a large number of developed countries.
Keywords: C10; C63; D12; E20; G50; I32; 330; absolute poverty measurement; household expenditures; statistical modeling